2001
DOI: 10.7164/antibiotics.54.967
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of the Rapamycin Producer Streptomyces hygroscopicus FC904.

Abstract: Rapamycin (RPM)is produced by Streptomyces hygroscopicus FC904 isolated from soil in Fuzhou, China. It is a triene macrolide antibiotic with potential application as an immunosuppressant and drug for human gene therapy. In an attempt to improve rapamycin production, mutation and screening of the parent culture have been carried out. Thousands of survivors were obtained after mutagenesis by NTG (3mg/ml) and UV (30W, 15cm, 30 seconds) of spore suspensions. None showed improved production of RPM. Wedetermined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The antitumor glycopeptide antibiotic zorbamycin produced from Streptomyces flavoviridis ATCC 21892 was enhanced through strain improvement by using UV radiation [22]. In another study, mutation and screening of the parent culture to improve rapamycin production were carried out [23]. It was reported previously that the lethality rate should be extremely high in order to have powerful mutations and effective screening of mutants.…”
Section: Discussionmentioning
confidence: 99%
“…The antitumor glycopeptide antibiotic zorbamycin produced from Streptomyces flavoviridis ATCC 21892 was enhanced through strain improvement by using UV radiation [22]. In another study, mutation and screening of the parent culture to improve rapamycin production were carried out [23]. It was reported previously that the lethality rate should be extremely high in order to have powerful mutations and effective screening of mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further improvement of the rapamycin titer and generation of diverse derivatives of rapamycin in S. hygroscopicus has been imperative for its commercial development and clinical applications. 62 In an attempt to improve rapamycin productivity, fermentation medium optimization as described in the previous section, 16,18,53,54 in addition to classical strain improvement, 63 protoplasts-related techniques 64 and high-throughput screening method 65 have been developed. Demain's research group obtained a higher rapamycin-producing mutant from the protoplasts of S. hygroscopicus FC904 mutants treated with 1 mg ml À1 of gentamicin, widely used aminoglycosides, where an HPLC analysis showed that the rapamycin titer for this mutant (139 mg l À1 ) was 60% higher than that for the parent strain.…”
Section: Mutagenesis and Mutasynthesismentioning
confidence: 99%
“…An enhanced productivity of rapamycin (194 mg l À1 ; 124% higher than that of starting strain) was also obtained when exposing the spores of the S. hygroscopicus FC904 strain to gentamicin and N-methyl-N¢-nitro-N-nitrosoguanidine. 63 Another attempt to generate high-yield rapamycin-producing strains was based on the protoplast-related techniques such as protoplasts mutation, intra-and interspecies fusion. When using mutation by UV, N-methyl-N¢-nitro-N-nitrosoguanidine, diethyl sulfates treatment or fusion of different parental protoplasts of S. hygroscopicus, progress was not achieved.…”
Section: Mutagenesis and Mutasynthesismentioning
confidence: 99%
“…The most useful combination of affecting factors is the chemical and physical mutagens (Rasouli and Kulkarni, 1994;Matseliukh, 1998;Cheng et al, 2001;Liu et al, 2003). Usually, the effectiveness of applied scheme of microbial producer selection is defined as a value of culture productivity increasing that varied from 1.5 to several tens of times.…”
Section: Introductionmentioning
confidence: 99%